A one-step bioprocess for production of high-content fructo-oligosaccharides from inulin by yeast. (20th October 2016) - Wang, Da; Li, Fu-Li; Wang, Shi-An
Highlights: Saccharomyces cerevisiae was used to produce fructo-oligosaccharides (FOS). The SUC2 gene was disrupted and an endo-inulinase gene was expressed in S. cerevsiae . A highest yield of 0.9 gFOS gInulin −1 was achieved by fermentation at 40 °C. A simple and efficient one-step bioprocess was established. Abstract: Commercial fructo-oligosaccharides (FOS) are predominantly produced from sucrose by transfructosylation process that presents a maximum theoretical yield below 0.60 gFOS gSucrose −1 . To obtain high-content FOS, costly purification is generally employed. Additionally, high-content FOS can be produced from inulin by using endo-inulinases. However, commercial endo-inulinases have not been extensively used in scale-up production of FOS. In the present study, a one-step bioprocess that integrated endo-inulinase production, FOS fermentation, and non-FOS sugars removal into one reactor was proposed to produce high-content FOS from inulin. The bioprocess was implemented by a recombinant yeast strain JZHΔS-TSC, in which a heterologous endo-inulinase gene was expressed and the inherent invertase gene SUC2 was disrupted. FOS fermentation at 40 °C from 200 g/L chicory inulin presented the maximun titer, yield, and productivity of 180.2 ± 0.8 g/L, 0.9 gFOS gInulin −1, and 7.51 ± 0.03 g/L/h, respectively. This study demonstrated that the one-step bioprocess was simple and highly efficient.